2013
DOI: 10.1039/c3ra42692k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hollow silica nanostructures using functional hairy polymer nanofibers as templates

Abstract: Hollow silica nanofibers and nanospheres were synthesized from functional hairy polymer nanofibers as sacrificial templates. The polymer nanofibers were isolated from a cylinder-forming polystyrene-block-poly(4-vinylpyridine) block copolymer using a selective-swelling approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The actual morphology for the PS(18500)-b-P4VP(40500) block copolymer, which was mostly used in this work, was confirmed using small angle X-ray scattering (SAXS) and TEM measurements (details in supporting information). The cylindrical domains were subsequently isolated in ethanol as nanofibers on which further sol-gel synthesis of titania shell was done using TTIP as the precursor [23,24]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actual morphology for the PS(18500)-b-P4VP(40500) block copolymer, which was mostly used in this work, was confirmed using small angle X-ray scattering (SAXS) and TEM measurements (details in supporting information). The cylindrical domains were subsequently isolated in ethanol as nanofibers on which further sol-gel synthesis of titania shell was done using TTIP as the precursor [23,24]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The important prerequisites here are sufficiently high χN value and strong solvent selectivity towards one of the block. Recently, we have shown that in the case of polystyrene-blockpoly(4-vinylpyridine) (PS-b-P4VP), the core-shell type of hairy nanofibers with PS core and hairy P4VP shell could be easily isolated in a solvent selective for P4VP block and without any additional cross-linking step [23,24]. These nanofibers potentially could be functionalized with a range of functional materials driven by the chemically active nature of the P4VP shell.…”
Section: Introductionmentioning
confidence: 98%
“…Such micelles comprising an inner PS core and outer P4VP corona can be obtained with the aid of P4VP-selective solvents, for instance, alcohols. Alcoholic PS- b -P4VP micellar solutions are particularly attractive for the synthesis of various polymer-inorganic core–shell, yolk–shell particles, or hollows particles, by exploring advantages of sol-gel processes [16,17,18]. Although the strong affinity of alcohols toward P4VP is known from the literature [11], to the best of our knowledge, there has been no effort to understand the effect of solvent on the PS- b -P4VP micellization process taking place in different alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…BCP micelles were used to accommodate various precursors and/or presynthesized nano-catalysts in specific domains, and also provides a low-cost option to deposit thin film on substrates, such as via evaporation and sputtering. BCPs having blocks capable of coordinating with metals or metal ions, like P4VP or P2VP [14][15][16][17], have been most frequently used for the templating of inorganic materials. The slow exchange kinetics in BCPr micelles allows an easy transfer of the micelles from colloidal solution onto a substrate by exploring different deposition methods, such as spin-coating or dip-coating.…”
Section: Micellar/colloidal Assembly And/or On-substrate Approachmentioning
confidence: 99%